2015
DOI: 10.1007/s00213-015-4004-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of NMDA receptors in the antidepressant-like effect of nicotine in mouse forced swimming and tail suspension tests

Abstract: Our study has for the first time confirmed that the antidepressant-like effect of nicotine on mice is NMDA-mediated, and nicotine presumably exerts this effect by antagonizing the glutamatergic NMDA receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 72 publications
2
18
1
Order By: Relevance
“…Furthermore, the NMDA receptor antagonists, such as (+)-MK-801 (0.3mg/kg) and CGP 37849 (5mg/kg), improved deficits in sucrose intake under the chronic mild stress model (Papp and Moryl, 1994), indicating possible antianhedonia effects for the NMDA receptor antagonists. Taken together, it is likely that (+)-MK-801 promotes antidepressant effects in rodent models of depression (Papp and Moryl, 1994; Haj-Mirzaian et al, 2015; this study), although these data are inconsistent with a recent report from Zanos et al (2016).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the NMDA receptor antagonists, such as (+)-MK-801 (0.3mg/kg) and CGP 37849 (5mg/kg), improved deficits in sucrose intake under the chronic mild stress model (Papp and Moryl, 1994), indicating possible antianhedonia effects for the NMDA receptor antagonists. Taken together, it is likely that (+)-MK-801 promotes antidepressant effects in rodent models of depression (Papp and Moryl, 1994; Haj-Mirzaian et al, 2015; this study), although these data are inconsistent with a recent report from Zanos et al (2016).…”
Section: Discussioncontrasting
confidence: 99%
“…It is reported that the NMDA receptor antagonists, including ketamine (1mg/kg) and (+)-MK-801 (0.05mg/kg), are able to attenuate the depression-like phenotype seen in the early-life social isolation stress model (Haj-Mirzaian et al, 2015), suggesting involvement of the NMDA receptor in the depression-like behaviors induced in this model. Furthermore, the NMDA receptor antagonists, such as (+)-MK-801 (0.3mg/kg) and CGP 37849 (5mg/kg), improved deficits in sucrose intake under the chronic mild stress model (Papp and Moryl, 1994), indicating possible antianhedonia effects for the NMDA receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons underlying the negative effect of ketamine are unknown, the experimental protocols (e.g., different animal models, experimental apparatus, dose of ketamine, and observational protocol) may contribute to the negative result. In addition, we did not perform the OF test after ketamine injection in the experiment 2 because the total distance, indicating the motor function in the OF test, is not affected by a single sub-anesthetic dose of ketamine in our previous studies 35, 47, 64 and other reports 46, 78 . Together, it seems that ketamine may not have beneficial effects on motor function deficits after SNI surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The criteria of considering the animals as immobile included stopping the struggle and staying immobile and floating in the water. After a 2 min adaptation period, the duration of immobility was measured in the last 4 min of the experiment …”
Section: Methodsmentioning
confidence: 99%